GAMBARAN GRIEFING PADA PEREMPUAN MUSLIM YANG DITINGGAL MENINGGAL SUAMI DI KABUPATEN ENDE, NUSA TENGGARA TIMUR - Hidayah, Rifa; Halida, Hilda; Aghniacakti, Ainindita (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aimed to describe the grieving process in women mourning for their husbands. This research uses a qualitative design with a phenomenological approach. The subjects consisted of three people, taken through purposive sampling technique with certain criteria. Data collection was carried out using in-depth interviews through interview guidelines made (semi-structured). At the initial stage, data reduction was carried out, then analyzing and presenting data and coding the interview transcripts. This study showed that the three respondents in this study had a positive view of their deceased husbands even though the loss was caused by different things. Their initial response after hearing the sad news was almost the same, namely shock and crying. After that, they tried to adjust and move on with their lives. Although they still feel a sense of longing, they are getting used to their new lives. Regarding the culture of remarriage, they are aware of it, but the subjects prefer to focus on the happiness of the children and let life go on over time.